CRIMINAL POLICY IN HANDLING SEXUAL VIOLENCE AGAINST CHILDREN BY THE PEMATANGSIANTAR RESORT POLICE - Suhaira Marbun; Rizkan Zulyadi; Andi Hakim Lubis (SOSIOEDUKASI, 2025)
Sexual violence against children is a very complex form of crime and has a long-term impact on the victim, both physically and psychologically. This study aims to analyze the comparison of legal regulations between sexual violence crimes and human trafficking crimes, evaluate the implementation of legal protection and criminal policies against sexual violence against children, and examine the countermeasures strategies carried out by the Pematangsiantar Resort Police. The method used is a normative juridical approach and a sociological juridical approach, by combining the study of laws and regulations and interviews with related parties. The results of the study show that although there are differences in characteristics between sexual violence and trafficking in persons, the two can be interrelated in the context of sexual exploitation of children. The Pematangsiantar Police have implemented criminal policies through preventive, repressive, and rehabilitative approaches. The strategies implemented include training investigators, provision of child-friendly spaces, and cross-sector collaboration with child protection institutions. Although there are still obstacles in terms of human resources and facilities, the efforts made show a strong commitment to providing legal protection for children as a vulnerable group. This research emphasizes the importance of criminal policies that are integrated with child protection approaches in order to provide comprehensive justice.